2008
DOI: 10.1007/s10681-008-9864-5
|View full text |Cite
|
Sign up to set email alerts
|

Starch characterisation and variability in GBSS loci of synthetic hexaploid wheats and their durum and Aegilops tauschii parents

Abstract: Greater variability in starch properties is found in lower ploidy wheats than in commercial hexaploid wheats. This paper reports on the starch properties and variability in granule bound starch synthase (GBSS) loci of 17 diploid (Aegilops tauschii) and 12 tetraploid (durums) potential progenitors of wheat, compared with 29 synthetic hexaploid wheats produced from such progenitors. Starch properties examined were granule size distribution, swelling power, amylose content, gelatinisation and amyloselipid dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
2
5
0
Order By: Relevance
“…The resulting synthesized hexaploids provide a rich source of genetic variation and can be readily hybridized with elite bread wheat cultivars and germplasm. Breeders have exploited these sources for resistance to a wide range of biotic and abiotic stresses (Adhikari et al 2003; Arraiano et al 2001b; Assefa and Fehrmann 1998, 2000, 2004; Berzonsky et al 2004; Cakmak et al 1999; Genc and McDonald 2004; Gororo et al 2001; Konik-Rose et al 2009; Lage et al 2003, 2004; Lage and Trethowan 2008; Mujeeb-Kazi et al 2001a, b; Sotelo et al 2009; Xu et al 2004, 2006). Here, we further investigate the potential of SHs and derived breeding lines as sources of resistance to M. graminicola in commercial resistance breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting synthesized hexaploids provide a rich source of genetic variation and can be readily hybridized with elite bread wheat cultivars and germplasm. Breeders have exploited these sources for resistance to a wide range of biotic and abiotic stresses (Adhikari et al 2003; Arraiano et al 2001b; Assefa and Fehrmann 1998, 2000, 2004; Berzonsky et al 2004; Cakmak et al 1999; Genc and McDonald 2004; Gororo et al 2001; Konik-Rose et al 2009; Lage et al 2003, 2004; Lage and Trethowan 2008; Mujeeb-Kazi et al 2001a, b; Sotelo et al 2009; Xu et al 2004, 2006). Here, we further investigate the potential of SHs and derived breeding lines as sources of resistance to M. graminicola in commercial resistance breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research showed that the synthetic hexaploid wheats had intermediate swelling power values, and tetraploid durums had the highest swelling powers, and the diploid Ae. tauschii had the highest gelatinisation peak temperatures ( Konik-Rose et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…The utilization of novel alleles of starch synthase genes in germplasm resources is very valuable for wheat breeding (Konik-Rose et al 2009;Guzmán et al 2011). These alleles could strongly affect the characterizations of starch for use in both food and non-food industries (Martin and Smith 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, in some instances, polymorphisms within starch genes that discriminate between wild and cultivated wheat have been identified Konik-Rose et al 2009;Shapter et al 2009), and several starch genes show strong purifying selection in maize (Manicacci et al 2007;Whitt et al 2002), sorghum (Hamblin et al 2007) and rice (Tian et al 2009). These studies focused on a limited subset of genes.…”
Section: Introductionmentioning
confidence: 99%